Implementation And Evaluation Of The Pacs System In The Radiology Department Of A Hospital: A Case Study In A Hospital In Indonesia - Sonia Ayu Islami; Anugrah Bagus Sugiharto (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the implementation and impact of the Picture Archiving and Communication System (PACS) in the Radiology Department of Wava Husada Hospital, focusing on operational efficiency, service quality, budget management, and satisfaction levels among patients and staff. A mixed-methods approach was employed, integrating both qualitative and quantitative research methods to provide a comprehensive analysis. The study assessed key variables, including operational efficiency, financial management, radiology image quality, service quality indicators, and satisfaction levels of both patients and staff involved in the PACS workflow. The findings indicate that the implementation of PACS resulted in improved operational efficiency, with an increase in the number of radiological procedures per working day and per working hour of radiographers. Financially, there was variation in revenue and cost realization, but the long-term benefits of PACS implementation outweighed the initial investment costs. Service quality indicators, such as the turnaround time for CT scan and chest X-ray readings, showed significant improvements. Additionally, the quality of radiology images improved, as evidenced by evaluations from radiology specialists. Patient and staff satisfaction regarding PACS services also yielded positive results, particularly concerning waiting times and clarity of diagnostic results. In conclusion, the implementation of PACS in the Radiology Department of Wava Husada Hospital positively affected operational efficiency, service quality, and satisfaction levels among both patients and staff. Although there was an increase in expenditure, the long-term benefits of the system justify the investment, making it a valuable asset for the hospital. Further evaluations of cost-benefit ratios are recommended, alongside continuous efforts to enhance service quality in line with technological advancements and regulatory standards.